2020
DOI: 10.1073/pnas.1918763117
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic Vibrio cholerae evolution and establishment of reservoirs in aquatic ecosystems

Abstract: The spread of cholera in the midst of an epidemic is largely driven by direct transmission from person to person, although it is well-recognized thatVibrio choleraeis also capable of growth and long-term survival in aquatic ecosystems. While prior studies have shown that aquatic reservoirs are important in the persistence of the disease on the Indian subcontinent, an epidemiological view postulating that locally evolving environmentalV. choleraecontributes to outbreaks outside Asia remains debated. The single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…Environmental populations of Vibrio cholerae , the etiological agent of cholera, are composed of different toxigenic and non-toxigenic lineages living together in brackish water habitats ( Pretzer et al, 2017 ; Mavian et al, 2020 ). Among their competitive arsenal, shared with ∼25% of all Gram-negative bacteria ( Bingle et al, 2008 ), is the type VI secretion system (T6SS).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental populations of Vibrio cholerae , the etiological agent of cholera, are composed of different toxigenic and non-toxigenic lineages living together in brackish water habitats ( Pretzer et al, 2017 ; Mavian et al, 2020 ). Among their competitive arsenal, shared with ∼25% of all Gram-negative bacteria ( Bingle et al, 2008 ), is the type VI secretion system (T6SS).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, persistent aquatic environmental reservoirs for V . cholerae O1 are present in Asia, causing a disease that has recurrently manifested in seven worldwide pandemics originating from Asia (Colwell & Huq, 1994; Mavian et al, 2020; Weill et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, ML methodologies are not equally effective for bacteria, detecting less ancestral states (nodes in the tree) than other approaches based on Bayesian inference. Nevertheless, and rather interestingly ML‐based methodology has been recently used for studying the evolution of Vibrio cholerae reservoirs in aquatic ecosystems (Mavian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In endemic countries, cholera continues to occur due to hot climate, poor sanitation and natural reservoirs of infection. Survival of TVC in such environments is thought to be the possible reason for recurrent annual epi demics in the Indian subcontinent [33]. Several investigations carried out in India during cholera outbreaks showed that TVC were present in samples collected from the affected areas [34][35][36].…”
Section: Toxigenic V Cholerae In the Environmentmentioning
confidence: 99%